Prediction of Block Production in Oil Palm Plantation Based on Canopy Cover Area and Vegetation Index Using Multispectral Aerial Photographs - Tri Haryo Sagoro; Andreas Wahyu Krisdiarto; Hermantoro Hermantoro (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
This study aims to develop an empirical estimation model of oil palm production through the canopy cover area approach and oil palm vegetation index with multispectral camera technology. The oil palm production estimation method was carried out by comparing the NDVI and NDRE index transformation algorithms. The basis for estimation an area of ± 0.3 ha. The results showed that there is relatively strong relationship between canopy cover area and FFB production (kg) with a coefficient of determination R² = 0.573. The results also revealed that NDVI value and the number of FFB have a fairly strong relationship with R² of 0.488. The NDRE value correlated to the number of FFB at a strong relationship with R² of 0.605. 4) the results of the analysis between NDVI Value and FFB Production (kg) have a strong relationship (r = 0.704) with a coefficient of determination of R² = 0.496; 5) the results of the analysis between NDRE Value and FFB Production (kg) have a strong relationship (r = 0.797) with a coefficient of determination of R² = 0.635; 6) The NDRE value is the independent variable that provides the best response, both to the Number of FFB and FFB Production (kg); 7) the best regression equation obtained for FFB production (kg) is Y(FFB Production (kg)) = 1153.8– (3621.9*NDRE); and 8) the best regression equation obtained for the number of FFB is Y(Number of FFB) = 113.98 – (379.53*NDRE). Keywords: Canopy cover area, Multispectral camera, NDRE, NDVI, Oil palm production.